Male and female condoms: What do women of a subnormal agglomerate know - Smalyanna Sgren da Costa Andrade; Ana Aline Lacet Zaccara; Kamila Nethielly Souza Leite; Maria Luísa de Almeida Nunes; Hemílio Fernandes Campos Coêlho; Simone Helena dos Santos Oliveira
Objective.Evaluate the knowledge about male and female condoms among women living in subnormal agglomerate and identify sources of information and appropriate care to use. Methods. Household survey, descriptive, transversal and quantitative study with 300 women over 18 of João Pessoa, Paraíba, Brasil, who began their sexual life. The systematic sampling plan for data collection was used. The interview form included sociodemographic questions and gazed relevant aspects of the use of condoms as a preventive measure of sexually transmitted infections and AIDS. Results. TV and healthcare professionals were the main sources of information. The participants knew more often the male condom features compared to women. The care most often mentioned by women as the use of male and female condoms were related to the validity, form of openness and conditions of packaging and storage of condoms. The largest number of care focused on measures taken in the pre-sexual moment. Moreover, care was nonspecific on the female condom. Conclusion: The participating women have inadequate knowledge on female and male condoms. It is necessary that the nursing seek health education strategies for improving knowledge about relevant information about male and female condoms.